Possible confounding factors on cerebral diffusion tensor imaging measurements. (20th February 2015) - Nenonen, Miina; Hakulinen, Ullamari; Brander, Antti; Ohman, Juha; Dastidar, Prasun; Luoto, Teemu M
Background: Diffusion tensor imaging (DTI) is prone to numerous systemic confounding factors that should be acknowledged to avoid false conclusions. Purpose: To investigate the possible effects of age, gender, smoking, alcohol consumption, and education on cerebral DTI parameters in a generally healthy homogenous sample with no neurological or psychiatric diseases. Material and Methods: Forty ( n = 40) subjects (mean age, 40.3 years; SD, 12.3) underwent brain DTI with 3 T magnetic resonance imaging (MRI). At enrolment, all the subjects were interviewed with respect to general health, education, history of smoking, and alcohol consumption. Studied DTI parameters included: (i) fractional anisotropy (FA); and (ii) apparent diffusion coefficient (ADC). Region-of-interest (ROI)-based measurements were estimated at 13 anatomical locations bilaterally on the axial images, except for the corpus callosum in which the ROIs were placed on the sagittal images. Circular ROI measurements were mainly used. Freehand ROI method was used with the forceps minor, uncinate fasciculus, and thalamus. Intra-observer variability and repeatability were assessed. Results: The most consistent finding was that aging decreased FA values in the frontal brain regions. Regarding the other confounding factors, the results were discontinuous and no concrete conclusions could be drawn from these findings. In general, intra-observer repeatability of the DTI measurement was considered relatively good. Conclusion: Age should be noted as considerable confounding factors in ROI-based DTI analysis. More research on the effects of gender, smoking, alcohol consumption, and education is needed.